Short- and long-term follow-up outcomes of patients with Brucella endocarditis: a systematic review of 207 Brucella endocarditis Cases. Issue 1 (1st January 2021) - Li, Xiufeng; Wang, Tan; Wang, Yuanzhi; Xie, Songsong; Tan, Wenbo; Li, Ping
ABSTRACT: Brucella endocarditis is a fatal complication and the most frequent cause of death for human brucellosis. This study aimed to systematically review the literature on the follow-up outcomes of Brucella endocarditis and analyze the determinants affecting the follow-up outcomes. The databases PubMed, Web of Science, Embase, and Cochrane were searched using keywords and suitable combinations. All studies reporting the follow-up outcomes of Brucella endocarditis were included. Finally, a total of 76 studies (207 patients), including cases or case series, were included. The event rate for patients who underwent short- and long-term follow-up was 12.0% (2 relapsed and 1 died) and 8.1% (6 relapsed and 8 died), respectively. The differences in outcomes between different age groups (18–39, 40–59, and ≥60) were significant ( P < 0.05, P = 0.035). The outcomes of the 18–39 age group were worse than those of the 40–59 age group (OR, 0.277; 95% CI, 0.103–0.748; P = 0.011). Accordingly, follow-up (both short- and long-term follow-up) is essential for Brucella endocarditis patients, especially for younger patients (18–39 years) in the first 6 months after treatment. The burden of Brucella endocarditis related complications were immense. Further studies are needed to explore age-based epidemiology of Brucella endocarditis and the exact influencing factors of the follow-up outcomes.